Exploring the Factors Influence the Usage of Private Transport at Ayer Keroh, Melaka: Factors Influencing the Usage of Private Transport - Loo, Heoy Shin; Chew, Boon Cheong; Yang, Yu Xin Ou (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Local authority’s council, Majlis Perbandaran Hang Tuah Jaya (MPHTJ), Melaka is aiming to reduce the traffic congestion and reduce Green House Gases (GHG) emission from private transport in Ayer Keroh. Ayer Keroh is selected as the research location because it consists of residential, industrial, commercial, state government administrative centre and tourist spot which cause it to be crowded with vehicles such as private cars, motorcycle, lorry and busses. Thus, the high usage of private transportation leads to serious traffic congestion and high emission of GHG in Ayer Keroh. Although effort to promote green transportation to reduce usage of private transport and GHG emission, most of the public in Melaka still prefer the usage of private transportation. Hence, the problems of traffic congestion and emission of GHG could not be reduced significantly. Therefore, this study aims to examine the factors influence the public to use private land transport in the area. The research design for this research is exploratory and mixed method (qualitative data and quantitative data source).Since the novelty of the research and MPHTJ does not implement any sustainable transport system in Ayer Keroh. The factors are lastly arranged based on the significant level by comparing the result from qualitative data and quantitative data: vehicle ownership, mobility substitute, vehicle cost, local neighborhood retail and service quality, walking and cycling conditions and health and environmental concerns. The data is further use for determination of strategies that change the public behavior in transport usage and proposing the sustainable transport planning.